Accessibility of Sekupang Port in Increasing The Level of Tourist Visits to Batam - Basri Fahriza; Lut Mafrudoh; Lintang Arya Bimo; Chaidir Musalam Rizkitha (Jurnal Siber Multi Disiplin, 2026)
The purpose of this study was to determine how much accessibility of Sekupang port in increasing tourist visits to Batam Island. The method used is to use qualitative methods with the Miles and Huberman interactive analysis model using four stages, namely; data collection, data reduction, data presentation and conclusions. The result obtained is that Sekupang Port has a close distance to Singapore but, this port is far from tourist centers in Batam because it is far from urban areas. And the ship route at Sekupang port is still 13 routes, previously there were 20 routes. Therefore, tourist visits through the port of Sekupang are not too crowded because they are inferior to other ports in Batam with locations closer to the city center and tourist attractions, even though the ticket prices offered are the same and the facilities and services themselves have accumulated.